Literatuur en crisis : de Vlaamse en Nederlandse letteren in de jaren dertig - Rymenants, Koen; Humbeeck, Kris; Robert, Jan; Stuyck, Jan (Antwerpen: AMVC-Letterenhuis, 2010)
"onder redactie van Koen Rymenants, Kris Humbeeck, Jan Robert, Jan Stuyck"